Peran Harga dan Kualitas pada Produk Skincare Sunscreen dalam Membentuk Prefensi Konsumen - Aqila, Kayla Tsabita; Sudrajat, Ajat (Jurnal Ilmiah Wahana Pendidikan, 2025)
The research aims to see how the role of product price and sunscreen product quality influences consumer preferences. This research is quantitative. The simple random sampling method was used to collect samples, namely 100 respondents in this study. To analyze the data, multiple linear regression analysis was used along with the t- and f test. Test results show that price does not influence consumer preferences for sunscreen products, while quality influences consumer preferences for sunscreen products. The calculation process was carried out using SPSS 25.